INTERNALIZATION OF ISLAMIC RELIGIOUS EDUCATION TO SHAPE THE RELIGIOUS CHARACTER IN THE MILLENIAL GENERATION AT DARUL FALAH KUDUS ISLAMIC BOARDING SCHOOL - Mukh Nursikin (Jurnal Cakrawala Ilmiah, 2022)
The purpose of this study was to determine the internalization of Islamic religious education to form religious character in the millennial generation of the Darul Falah Islamic boarding school students in Kudus. Those born between 1980-2000 are the millennial generation. This generation has characteristics like Existence, requires more attention, likes to have opinions, grows an image, adds insight, likes freedom, likes to personalize, relies on the speed of instant information (ready to serve), likes to learn, works in an innovative environment, actively collaborates, hyper technology, critical, confidence, connected, lazy, not deep, not grounded, or not sociable. The research used is descriptive analytic with a qualitative research approach, and also uses the theory of experts about Islamic education in character building. The results of the study revealed that the internalization of Islamic religious education in the millennial generation to form religious character at the Darul Falah Kudus Islamic Boarding School teaches values ​​to the Millennial Generation of students including compassion, helping, not being ghosob (borrowing without permission), understanding morality, inculcating values. The Qur'an and Hadith are more in-depth, inculcating the values ​​of local wisdom, namely the pesantren tradition